Feijóo Versus Abascal: Generation Z, corruption and politics’ attributes perception: a correlational study with Implicit Association Test IAT - Martín Díez, Pablo; García Pérez, Eloy; Simón Sandoval, Pamela (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
ZThe political behavior of generation Z is based on animosity, distrust of traditional parties and a preference for new movements. This article uses Implicit Association Test (IAT) methodology, to compare how generation Z perceives Santiago Abascal, the leader of the emerging party Vox, and Alberto Núñez Feijóo, recently appointed president of the Popular Party, in Spain, with the aim of evaluating its attributes (positive and negative) and measuring the implicit perception of a possible link to corruption, and all this within an electoral projection framework.